Feasibility of an Asian Currency Unit - Abhijit Sen Gupta; Amitendu Palit (Indian Council for Research on International Economic Relations (ICRIER), 2008)
In this paper we evaluate the feasibility of a common Asian Currency Unit (ACU) involving countries of East and South Asia. We analyze the various properties of an ACU and calculate it's value using weighted averages of the values of Asian currencies. Looking at the movement of individual Asian currencies vis-'a-vis the ACU, we find that there have been severe misalignments among the Asian currencies during the past seven years. We discuss the possibility of the Rupee figuring in the ACU and identify the major economic, political and historical impediments in the way of faster acceptance of ACU in the region. We point out the various strategies that could be employed to facilitate faster adoption of ACU. These include creating certain institutional safeguards as well as strengthening the existing ones. Finally, we highlight some ways to promote the use and acceptability of the ACU and also emphasize the importance of conceiving a larger framework of participating countries, including India.
Keywords: F36; F41; 330; Asian Currency Unit; Regional integration; Monetary cooperation; Währungsunion; Optimaler Währungsraum; Wirkungsanalyse; Prognose; Asien